Muslims of the Dutch East Indies and the Caliphate Question - Martin van Bruinessen (Center for Study of Islam and Society (PPIM) Syarif Hidayatullah State Islamic University, 1995)
The abolition of 'Abd al-Majid's caliphate by Turkey's national assembly in March 1924, and the call by Azhar 'ulama' for an international congress in Cairo to elect a new khalifah the following year, had the effct of making Muslims in the Dutch Indies more aware that they were living under infildel rule. These events, and the conquest of the Hijaz by Ibn Sa'ud in the same year, briefly caised feverish activity the Indies. The interm advisor on native affairs to the Dutch Indies goverment, R.A. Kern, even spoke of 'a milestone in the Muhammadan movement in this country.